Impact of dyadic practice on the clinical self-efficacy and empathy of nursing students - Maryam Kamali; Shirin Hasanvand; Parastou Kordestani-Moghadam; Farzad Ebrahimzadeh; Mitra Amini (BMC, 2023)
Abstract Background Dyadic practice of learners creates supportive learning. So far, few studies have investigated the impact of this approach on students' empathy and self-efficacy. This study aimed to investigate the effect of dyadic practice on nursing students' clinical self-efficacy and empathy. Methods This study was based on a pretest-posttest randomized group from September to December 2018. All the junior nursing students (n = 44) were divided into intervention (n = 22) and control groups (n = 22) using stratified random sampling. The intervention group was trained for 6 days as student dyads, while the control group was under the supervision of an instructor and worked individually. The students' levels of empathy and self-efficacy were evaluated on the first day (pretest) and the last day (post-test) by The Self-Efficacy in Clinical Performance Scale and Mehrabian and Epstein empathy scale. The data were analyzed using the SPSS software by Fisher's exact test, Mann-Whitney test, independent t-test paired t-test, Wilcoxon signed-rank, and Analysis of covariance. Results Dyadic practice increased empathy in the intervention group compared to the control group (P < 0.001). The adjusted mean of total empathy in the intervention group was 21.1 degrees higher than the adjusted mean of total empathy in the control group. However, no significant differences were found between the two groups in clinical self-efficacy (P = 0.762). Conclusions The employment of this approach seems helpful in creating an empathic atmosphere. However, further studies are required to prove the effectiveness of this method on self-efficacy.